Analysis Determinant Dengue Hemorrhagic Fever (DHF) Incidents in the Work Area Sako Health Center Palembang City in 2024 - Tania Ovelina; Gema Asiani; Nani Sari Murni (Lembaga Pengembangan Kinerja Dosen, 2025)
Incident fever bloody globally increasing​ sharp. Death consequence fever bleeding in Indonesia from 725 cases in 2020 increased to 1,227 cases in 2022. Study aiming analyze factor affecting​ DHF incidents in the work area Sako Health Center Palembang in 2024. Research conducted in March 2024. Research design quantitative with cross sectional approach. Population that is all KK in the work area Sako Health Center has 9,584 people. A sample of 99 people was taken use cluster random sampling technique with Single-Stage Cluster Sampling. Research results influence knowledge (p value 0.011), influence attitude (p value 0.351), influence behavior clean bathtub (p value 0.603), influence condition container (p value 1.000), influence existence larvae mosquitoes (p value 0.035), influence use wire gauze (p value 0.054) and influence role government (p value 0.095) against DHF incidents in the work area Sako Health Center, Palembang. Multiple logistic regression test results obtained knowledge (p value 0.001), existence larvae mosquitoes (p value 0.022), use wire gauze (p value 0.014) and role government (p value 0.028). There is influence knowledge and existence larvae mosquito to DHF incidents. The most dominant factor to the incidence of dengue fever is knowledge. Recommended For increase effort prevention of dengue fever with do action prevention in a way real and sustainable.